2010
DOI: 10.1063/1.3474639
|View full text |Cite
|
Sign up to set email alerts
|

Patterning nanowire and micro-/nanoparticle array on micropillar-structured surface: Experiment and modeling

Abstract: DNA molecules in a solution can be immobilized and stretched into a highly ordered array on a solid surface containing micropillars by molecular combing technique. However, the mechanism of this process is not well understood. In this study, we demonstrated the generation of DNA nanostrand array with linear, zigzag, and fork-zigzag patterns and the microfluidic processes are modeled based on a deforming body-fitted grid approach. The simulation results provide insights for explaining the stretching, immobilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 16 publications
(13 reference statements)
0
32
0
Order By: Relevance
“…The numerical scheme used to solve these coupled governing equations is based on a finite volume discretization. Details of the mathematical model and the numerical scheme can be referenced in our previous work [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…The numerical scheme used to solve these coupled governing equations is based on a finite volume discretization. Details of the mathematical model and the numerical scheme can be referenced in our previous work [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…For non-circular micropillars, the hydraulic diameter (D h ) is adopted to characterize the size of the micropillars instead of D p . The value of h w has little influence on the size of the microdroplets, provided it does not exceed a critical depth [12]. The typical grid adopted in the numerical simulation was 0.7×10 6 hexahedral cells to discretize the computational domain for a row array arrangement consisting of five micropillars, see Figure 2.…”
Section: Mathematical Model and Numerical Methodsmentioning
confidence: 99%
“…They examined the effects of polymer concentration and roller speed on the diameter of polymer microdroplets and their lateral spacing. In a previous study of the authors [12], a microdroplet array was successfully created on a micropillar-featured surface and also the corresponding dewetting process as modeled using a numerical approach, where the mechanism for the formation of the microdroplets on the columns of the micropillars was clarified as well. It was also demonstrated that the size of the nanoparticles created after evaporation of the fluid was controlled by the volume of the microdroplets and the concentration of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this deposition process can only be controlled through controlling the dynamics of the carrier liquid film, and, in particular, the evolution of the morphology of the triple line. In a recent study, DNA molecules were deposited in a highly ordered array by dissolving them in a solvent and letting the solvent dewet a micropillar-structured surface [9].…”
Section: Introductionmentioning
confidence: 99%